Ageing-related changes in cognitive functions and their associations with event-related potentials and physical fitness in healthy older adults - Mannila, Heikki; Vainio, Juhani (2019)
Ageing manifests at least on the levels of structural degradation of the brain, as well as a slight cognitive decline even in healthy older adults. It is widely recognized that better physical fitness helps preserve cognitive abilities in older age and delay the inevitable cognitive decline. In this follow-up study, we investigated in what relation cognitive abilities, physical fitness and event-related potentials (ERPs) develop over approximately five years, and whether the development of cognitive abilities is possible to be predicted with the baseline of physical fitness or the ERPs. Out of the 90 older women who participated in the baseline measurement, 35 participated in this follow-up. We measured ageing-sensitive ERPs with an electroencephalography (EEG) to either somatosensory tactile stimulation or auditory sinusoidal sound stimulation. To assess the participants’ cognitive capacity, we conducted a battery of neuropsychological tests that assessed cognitive domains sensitive to ageing. In addition to these, the participants carried out a six-minute walk test to measure their aerobic physical fitness. The somatosensory P3a and the auditory P2 showed significant change over time, which reflects their ageing-sensitive nature. Decreased six-minute walk test distance was associated with a decline in explicit memory. The enlargement of the auditory P2 standard response associated with improved explicit memory, indicating neural compensation. In addition, the enlargement of the deviant response of the auditory P2 associated with worsened six-minute walk test performance. Attenuation of the deviant response of the somatosensory P3a associated with a prolonged performance time in Stroop 3 test. Higher baseline of six-minute walk test performance predicted better preservation of explicit memory. Additionally, higher (more negative) baseline of the auditory N1 predicted improvement in explicit memory performance and an increase in error susceptibility. The results of this longitudinal study indicate a connection between aerobic physical fitness and explicit memory. Additionally, we got further support indicating that the auditory P2 seems to be linked to neural compensation, as activity in fronto-central topography increased as well from the baseline measurement to the follow-up. The somatosensory P3a seems to be associated to executive functions and attentional modulation. Better preservation of explicit memory was able to be predicted with the baseline of physical fitness. In addition to P2, the predicting ability of N1 on cognitive preservation may reflect neural compensation in older adults. The results of the present study are of great importance to older adults who wish to maintain their cognitive abilities for as long as possible, and to other researchers, as valuable evidence of complicated ageing-related processes.